2016
DOI: 10.3390/nano6110219
|View full text |Cite
|
Sign up to set email alerts
|

The Dispersion State of Tangled Multi-Walled Carbon Nanotubes Affects Their Cytotoxicity

Abstract: The medical applications of carbon nanotubes (CNTs) have garnered much attention. However, evaluating the safety of CNTs remains difficult, and no consensus has been reached. Moreover, assessing the biosafety of multi-walled CNTs (MWCNTs), which can become tangled during manufacturing, is challenging because they do not readily disperse. We studied how the dispersion state of tangled MWCNTs affects their cytotoxicity, using three sonicators. Flotube 9110 (FT9110), tangled MWCNTs, were dispersed in two dispersa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…In our previous studies, we reported that different types of CNTs were incorporated into cells 31 and that the same CNTs affected the uptake into cells due to the dispersed state of particles. 21 In this study, like our previous study, we found that the aggregated CNT was incorporated into RAW264 cells, but that the amount of material taken up differed dramatically between highly dispersed FT9110 and CNHs showing the Notes: cultured raW264 cells were exposed to FT9110 at 10 µg/ml. The control was medium containing each dispersant only.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In our previous studies, we reported that different types of CNTs were incorporated into cells 31 and that the same CNTs affected the uptake into cells due to the dispersed state of particles. 21 In this study, like our previous study, we found that the aggregated CNT was incorporated into RAW264 cells, but that the amount of material taken up differed dramatically between highly dispersed FT9110 and CNHs showing the Notes: cultured raW264 cells were exposed to FT9110 at 10 µg/ml. The control was medium containing each dispersant only.…”
Section: Discussionsupporting
confidence: 78%
“…Evaluation of highly dispersed CNTs and aggregated tangled CNTs using carcinogenic human bronchus cells demonstrated that only aggregated CNTs were taken up by cells and showed growth suppression. 21 However, for macrophages, which are believed to affect the carcinogenicity of CNTs, 19 few studies have investigated the effects of fully dispersed tangled CNTs on cell proliferation and immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…The oxidation of MWCNTs’ surface increases their solubility and dispersion rate [ 45 ]. It was also shown that better dispersion decreases the cytotoxity of MWCNTs [ 46 ]. In the present work we have shown for the first time that MWCNTs degrade mostly from the inner side upon sodium hypochlorite treatment.…”
Section: Discussionmentioning
confidence: 99%
“…We have already reported that the dispersion state of CNMs affects some cell lines differently [29,30]; accordingly, we first examined the dispersion state of the CNMs used in the aqueous solution. The sonicated CNMs were measured with a Zetasizer Nano ZS first (Table 1), and their shapes were observed with a TEM (Figure 1).…”
Section: Characterization Of Dispersed Cnmsmentioning
confidence: 99%